Time kinetics of physical activity, sitting, and quality of life measures within a regional workplace: a cross-sectional analysis - Daniel B. Lindsay; Sue Devine; Rebecca M. Sealey; Anthony S. Leicht (BMC, 2016)
Abstract Background Interventions to increase physical activity and reduce sedentary behaviours within the workplace have been previously investigated. However, the evolution of these constructs without intervention has not been well documented. This retrospective study explored the natural progression or time kinetics of physical activity, sedentary behaviours and quality of life in a professional skilled workplace where focussed interventions were lacking. Methods Participants (n = 346) employed as full-time staff members at a regional university completed an online survey in 2013 assessing physical activity and sedentary behaviours via the International Physical Activity Questionnaire, and quality of life via the Short-Form 36v2 questionnaire. Differences between that cohort of participants and an initial sample of similar participants (2009, n = 297), accounting for gender and staff categories (academic vs. professional), were examined using ANCOVAs with working hours as a co-variate. Results In comparison to the initial cohort, the follow-up cohort reported significantly less leisure-time, total walking, total vigorous and total physical activity levels, and lower overall physical health for quality of life (p < 0.05). In contrast, the follow-up cohort reported a significantly greater weekly sitting time, greater mental health scores for quality of life and greater total moderate physical activity levels (p < 0.05) compared to the initial cohort. Conclusions Over a 4-year timeframe and without focussed workplace interventions, total physical activity levels were lower with sedentary behaviours greater at a rate twice that reported previously. Continuation of these undesirable health behaviours may impact negatively on worker productivity and health at a greater rate than that currently reported. Workplace interventions targeting sedentary behaviours and physical activity should be actively incorporated into organisations to counteract the alarming behavioural trends found in this study to maintain and/or enhance employee health and productivity.